Bicuspid aortic valve associated aortopathy: a genetic disease? - Ciro Bancone; Marisa De Feo; Alessandro Della Corte (Cardiogenetics, 2015)
The present paper briefly reviews the literature supporting the pathogenetic importance of hemodynamics in the development of bicuspid aortic valve-associated aortopathy. The hypothesis of a genetic basis for this disease, whether it is a common defect for bicuspid malformation and predisposition to aortic aneurysm or not, should not be discarded. However, a more complex, multifactorial pathogenesis model is here proposed, based on the hypotheses raised by recent studies both on clinical and pre-clinical aspects of bicuspid aortopathy, whereby in at least some forms of the disease the biomechanical factors capable to induce aortic wall maladaptive remodeling may be necessary to the development of the aortopathy. The main scope of this review is to underscore the importance of trying to advance the scientific knowledge not only on the genetic bases but also on the peculiar aspects of hemodynamics of bicuspid aortic valve and flow-induced vascular remodeling.